The force of questioning and pragmatic strategies in courtroom interrogation: A conversation analysis - Anisah Anisah; Diana Fauzia Sari (Universitas Syiah Kuala, 2024)
This is a conversation analysis study on courtroom communication. This study aims to investigate how the forces of question (information seeking and confirmation seeking) were achieved and the pragmatic strategies, particularly repetition, and reformulation, used by the prosecutor during a cross-examination of the defendant in an Indonesian murder case; a courtroom trial of a cyanide poisoning case considered weak due to a lack of sufficient evidence against the defendant. The data was obtained from the Kompas TV YouTube Channel and was transcribed using Jeffersons (2004) technique of transcription. This study employed a descriptive qualitative method to discover the force of questions and pragmatic strategies. The data was analyzed by adapting Gibbons (2003) and Archer's (2005) classification of question form and question force. The results demonstrate both information-seeking and confirmation-seeking questions were used by the prosecutor. Gibbons (2003) repetition and reformulation strategies were used to further investigate the pragmatic strategies. The finding shows pragmatic strategies, particularly repetition, and reformulation, were also evidenced in the lines of questioning. The patterns of the findings indicate that the prosecutor attempted to portray the defendants unreliability and untrustworthiness in court. These findings also implicate that the existence of the strict rules of courtroom communication and power imbalance in court allows the prosecutor to influence the defendants response.